(untitled) (Journal of Fatima Jinnah Medical University, 2022)
Background: Construction industry is one of the most hazardous and accident prone occupation causing around 270 million accidents and 2 million deaths annually. In Pakistan reporting of incidence of occupational injuries and accidents is low. The present study aimed to determine the physical and mental health profile of construction workers in Lahore, Pakistan. Subjects and methods: An analytical cross-sectional study was conducted among construction workers in Lahore from January 2020 to September 2020. The study included 181 participants by using non-probability convenience sampling technique. Data was collected by using a self-structured, pre-tested questionnaire. Data was analyzed using SPSS version 23. Chi-square test was applied and p-value <0.05 was taken as significant to find out association with duration of occupational exposure. Results: Maximum number of the participants 55 (30.4%).was between age group 26-35 years and 97 (53.6%) were illiterate. Among 181 participants, 112 (61.87%) were found to be hypertensive, 98 (54.1%) were drug abusers. The total duration of hours spent on work per day was reported more than 10 hours in 50 (27.6%) of the participants. A significant association was observed between duration of occupational exposure and presence of chronic illnesses (p value=0.028) and mental health issues (p=0.041). A significant association (p-value= 0.026) was also found with duration of exposure with drug abuse. Bad effect of health on job performance was reported by 97 (53.6%) of the workers and 71(39.2%) of the workers reported restricted movements after injury during occupational exposure. Conclusion: In this study, a relatively higher prevalence of chronic diseases, injuries and stress has been reported by construction workers, negatively affecting their occupation. Significant associations are seen with duration of exposure and its impact on physical and mental health.